Gluteal muscle activation during rehabilitation exercises in female field hockey players - Daretha Coetzee; Frederik F. Coetzee; Robert Schall; Colleen Sinclair (South African Journal of Physiotherapy, 2021)
Background: Field hockey, a team sport played by both men and women at both recreational and professional levels, requires maintaining a forward flexed posture putting stress on the lumbar spine. Hence, it is necessary to assess the muscles supporting the lumbar spine, especially those surrounding the hip, to inform strengthening exercises for this population.